Unveiling Organocatalysts Action – Investigating Immobilized Catalysts at Steady‐State Operation via Lab‐on‐a‐Chip Technology. Issue 24 (7th September 2021) - Westphal, Hannes; Warias, Rico; Becker, Holger; Spanka, Matthias; Ragno, Daniele; Gläser, Roger; Schneider, Christoph; Massi, Alessandro; Belder, Detlev
Abstract: This paper reports a new method for studying stereoselective catalyzed reactions at a small scale. For this purpose, a micro‐sized chemical reactor and a chiral chromatographic column were integrated on a single microfluidic chip hyphenated to mass spectrometry. By running the integrated reactor in truly continuous‐flow operation with an automated injection strategy, catalytic processes and their stereoselectivity can be observed over an extended range of time with significantly small consumption of samples, solvents, and catalytic material. Abstract : Continuous‐Flow Catalysis : Herein, we present a novel method that combines continuous‐flow catalysis and on‐line HPLC/MS‐analysis on one single chip device. In addition to investigating the durability of immobilized organocatalysts, their dynamic course of stereoselectivity and steady‐state can be studied while minimizing resource consumption and waste production.